The Innovative Learning System Design: Integrating Guided Inquiry and Flipped Classroom Using Discord For Fundamental Laws of Chemistry - Dafista, Nara; Mawardi, Mawardi; Suryani, Okta; Akmar, Reza (PT Inovasi Pratama Internasional, 2025)
The material of the basic laws of chemistry is an important foundation in understanding various advanced concepts in chemistry, especially those related to quantitative calculations such as the concept of moles. However, the abstract and mathematical characteristics of the material are often an obstacle for students in understanding the concept thoroughly. The purpose of this research is to develop a guided inquiry-based learning system integrated with flipped classroom assisted by Discord application on the material of basic laws of chemistry. The research employed the Educational Design Research (EDR) method using the Plomp model, which includes three stages:preliminary research, development or prototyping phase, and assessment phase, with limitations up to the small group trial stage (prototype IV). The research subjects consisted of 3 lecturers, 2 chemistry teachers, and 9 students of class XI SMAN 8 Padang. Needs analysis revealed that chemistry learning remains abstract and heavily mathematical, leading to student difficulties and misconceptions. To address this, a learning approach was designed incorporating three levels of multiple chemical representations (macroscopic, submicroscopic, and symbolic) integrated flipped classroom that supports independent learning, with guided inquiry syntax. Discord was selected as the supporting platform due to its comprehensive features that facilitate both synchronous and asynchronous learning. The product was tested through validation by experts and evaluation of students. The results of content validity of 0.89 and construct validity of 0.93 indicate that the product is valid. The practicality value of 93% obtained from the analysis of the practicality questionnaire of teachers and students with a very practical category. These findings suggest that the developed learning system is appropriate for use in chemistry education and can effectively help students independently and meaningfully understand the basic laws of chemistry. Furthermore, this study supports the implementation of the Merdeka Curriculum and the integration of technology-based learning.